High-strength seawater-corrosion-resistant chain steel, chain and manufacturing method of high-strength seawater-corrosion-resistant chain steel
By rationally designing chemical components in chain steel and using quenching heat treatment and hot coating treatment processes to form a specific microstructure, the problem of mismatch in strength, tough plasticity and corrosion resistance of the chain is solved, and chain steel with high strength, good toughness and excellent seawater corrosion resistance is achieved.
Patent Information
- Application Number
- CN202311283362.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing chains do not match strength, tough plasticity and corrosion resistance, which affects service life, and are more prominent in marine environments.
By designing the chemical components of high-strength, seawater corrosion-resistant chain steel, including elements such as C, Si, Mn, Cr, Ni, Mo, Al, V and N, and using quenching heat treatment and hot coating treatment processes, a microstructure of needle-like tempered martensite and dispersed carbides are formed.
It achieves the high strength and tough plasticity matching of chain steel, while having excellent seawater corrosion resistance, extends the service life of the chain, and is suitable for the manufacturing of high-strength corrosion-resistant structural parts, etc.
Smart Images

Figure CN119710482A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chain steel and chains, and in particular to a high-strength seawater corrosion-resistant chain steel and chain and a manufacturing method thereof. Background Art
[0002] About 1 / 6 of the world's annual steel production is lost due to corrosion. The direct economic losses caused by steel corrosion in my country exceed 10 billion yuan each year. In addition, steel corrosion reduces the service life of steel structures, causes casualties and economic losses, and causes environmental pollution. Especially in the marine environment, chloride ions in seawater and sea surface air are particularly serious for steel corrosion during service. In order to improve the corrosion resistance of steel, coating and plating are usually carried out on the surface of steel. Although it can effectively delay the corrosion process, once defects appear on the surface of the coating during the service of steel, the steel will corrode in the middle of the coating, causing the coating to fail quickly. Although stainless steel has excellent corrosion resistance, the addition of a large number of alloying elements leads to high costs, making it impossible to be used on a large scale. Therefore, low-alloy corrosion-resistant steel has received more and more attention due to its relatively low alloy content, excellent mechanical properties and relatively good corrosion resistance. With the vigorous development of my country's ocean shipping and marine engineering construction, higher and higher requirements are also put forward for the strength and corrosion resistance of steel, and the demand for high-strength chain steel with excellent seawater corrosion resistance is increasing.
[0003] At present, many seawater corrosion-resistant steels have been developed both at home and abroad, mainly by optimizing the alloy elements such as Cr, Ni, Cu in the steel to improve the seawater corrosion resistance of the steel. For example, Chinese patent CN201010266527.0 discloses an ultra-high strength ship plate steel and a production method thereof. The slab composition is: C: 0.02-0.09%, Si: 0.1-0.4%, Mn: 0.5-1.6%, Alt: 0.01-0.04%, Nb: 0.02-0.05%, Ti 0.008-0.02%, Cr 0.3-0.7%, Mo0.2-0.5%, Ni 0.5-1%, Cu0.2-1%, P < 0.013%, S < 0.005%, O < 0.0012%, N < 0.0045%, H < 0.00015%. The ultra-high strength ship plate steel is produced by controlled rolling and controlled cooling technology + subsequent heat treatment, with a tensile strength greater than 670MPa and an impact energy greater than 200J at -60°C. Chinese patent CN201180066512.2 discloses an ultra-high strength structural steel, whose chemical composition is C: 0.07-0.12%, Si: 0.1-0.7%, Mn: 0.5-2.0%, Ni: 0.8-4.5%, Cu: 0.25-3.0%, Cr: 0.5-1.6%, Mo: <0.8%, and Ti: 0.04%, as well as iron and inevitable impurities; this technology adds a higher content of Ni, Cu, Cr, and Mo alloy elements to a relatively low carbon content, adopts a hot rolling controlled cooling process, and directly quenches to a temperature not exceeding 450°C at a cooling rate of 20-150°C / s after hot rolling. The final steel yield strength is greater than 960MPa, and the impact energy of the -40°C welding heat affected zone is greater than 34J. Chinese patent CN201610993472.0 discloses a high-strength, high-toughness, corrosion-resistant chain steel, whose chemical composition is C: 0.06-0.11%, Si: 0.15-0.35%, Mn: 0.30-0.50%, Cr: 1.00-3.00%, Ni: 2.00-4.00%, Mo: 0.30-0.60%, Nb: 0.02-0.06%, V: 0.03-0.09%, P<0.015%, S<0.015%, and the balance is Fe and unavoidable impurities. ; This technology adopts a process of two quenching heat treatments and one tempering heat treatment to obtain a lath martensite structure with a lath width of 0.3 to 5μm. Granular cementite with a diameter of 0.2 to 0.8μm and a volume fraction of 0.15% to 0.35% and MC phase particles with a diameter of 5 to 15nm and a volume fraction of 0.02% to 0.08% are dispersed between and inside the laths; the tensile strength of the chain after heat treatment reaches 1000MPa, the KV2 (-60℃) of the ring back and weld reaches more than 100J, and the seawater corrosion resistance is good.
[0004] In addition, there are some weathering steel products for certain special service environments. For example, Chinese patent CN201611102046.X discloses a high-strength weathering steel for high-humidity and high-heat marine atmospheric environment. Its chemical composition (wt%) is C: 0.01-0.03, Si: 0.30-0.50, Mn: 0.60-0.80, Cu: 0.90-1.10, Ni: 2.80-3.20, Mo: 0.20-0.40, Sn: 0.25-0.35, Sb: 0.05-0.10, Cr≤0.03, Nb ≤0.02, P≤0.01, S≤0.01, RE: 0.03~0.05, and the rest is Fe; based on the Cu-Ni-Mo alloy system, this technology greatly reduces the Cr content in weathering steel by adding multiple micro-alloying elements such as Sn, Sb, Nb, RE, etc.; by controlling the cooling rate of the steel to 12~17℃ / s and cooling to 530~570℃ for insulation after hot rolling, acicular ferrite and polygonal ferrite structures are formed, and the yield strength of the steel is greater than 650MPa and the tensile strength is greater than 750MPa, and the half-size impact energy at 30℃ is greater than 65J.
[0005] Referring to the above-mentioned prior art, it can be seen that the existing seawater corrosion-resistant high-strength steel products mainly improve the seawater corrosion resistance of the substrate by optimizing the alloy composition, and the yield strength is mostly around 600-900MPa, and there are very few high-strength seawater corrosion-resistant steel products with a yield strength exceeding 1000MPa.
[0006] Based on this, the present invention hopes to obtain a new type of high-strength seawater corrosion-resistant chain steel, which can combine the chain heat treatment process with the coating process. The finished chain has excellent comprehensive performance. It not only has high strength, but also has excellent toughness and plasticity matching. The chain has excellent corrosion resistance and can well solve the problem of existing chains that the service life is affected by the mismatch of strength, toughness, plasticity and corrosion resistance. Summary of the invention
[0007] In view of the problem that the service life of existing chains is affected by the mismatch between strength, toughness, plasticity and corrosion resistance, the purpose of the present invention is to provide a high-strength seawater corrosion-resistant chain steel and chain and a method for manufacturing the same. By designing the components and optimizing the manufacturing process, the high-strength seawater corrosion-resistant chain steel has high strength while also having good toughness-plasticity matching and excellent seawater corrosion resistance. It is particularly suitable for manufacturing high-strength corrosion-resistant structural parts, industrial products for mining, mooring and other purposes, and can be widely used in environments with a large number of corrosive media such as engineering machinery, mines, ships and marine engineering.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] The first aspect of the present invention provides a high-strength seawater corrosion-resistant chain steel, comprising the following chemical components in mass percentage: C: 0.25-0.35%, Si: 0.1-0.6%, Mn: 0.3-0.9%, Cr: 0.3-1.2%, Ni: 1.8-3.2%, Mo: 0.4-1.0%, Al: 0.02-0.05%, V: 0.08-0.30%, N: 0.009-0.02%, and the balance is iron and unavoidable impurities.
[0010] Preferably, its composition meets the following requirements: 1.3*Ni+2*Cr+7*Mo+0.5*Si+V≥8, wherein Ni, Cr, Mo, Si, and V are the values before the percentage sign of the mass percentage content of the corresponding elements.
[0011] Preferably, among the unavoidable impurities, P≤0.015%, S≤0.01%, and O≤0.002%.
[0012] Preferably, the austenite grain size of the high-strength seawater corrosion-resistant chain steel is ≥ grade 7; after quenching heat treatment and hot-dip coating treatment, the microstructure of the high-strength seawater corrosion-resistant chain steel is needle-shaped tempered martensite and dispersed carbides.
[0013] Preferably, its performance meets the following requirements: yield strength Rp 0.2 ≥1000MPa, tensile strength R m ≥1100MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J.
[0014] Preferably, after the surface of the high-strength seawater corrosion-resistant chain steel is treated with hot-dip plating, the corrosion rate is ≤0.2g / m after a 5% NaCl neutral salt spray corrosion test for 120h. 2 .h.
[0015] The second aspect of the present invention provides a high-strength seawater corrosion-resistant chain manufactured using the high-strength seawater corrosion-resistant chain steel according to the first aspect of the present invention, and its performance meets the following requirements: Rp 0.2 ≥1000MPa, tensile strength R m ≥1100MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is ≤0.2g / m 2 .h.
[0016] The third aspect of the present invention provides a method for manufacturing the high-strength seawater corrosion-resistant chain as described in the second aspect of the present invention, comprising the following steps:
[0017] S1, smelting and casting;
[0018] S2, hot rolling, control the compression ratio of the material ≥10;
[0019] S3, ring welding;
[0020] S4, quenching heat treatment, the heating temperature of quenching heat treatment is 850-950℃, the holding time is 1-3h, and water cooling quenching is adopted;
[0021] S5, pickling pretreatment;
[0022] S6, hot dip galvanizing, the chain after pickling pretreatment is preheated and then hot dip galvanized to obtain a high strength seawater corrosion resistant chain, and the temperature difference between the preheating temperature of the preheating treatment and the galvanizing solution used for the hot dip galvanizing is controlled to be -30 to 30°C.
[0023] Preferably, in step S1, the smelting includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment; and the casting adopts a continuous casting process.
[0024] Preferably, in step S1, the vacuum treatment time of the VD or RH vacuum treatment is 10 to 20 minutes; during the casting process, the superheat of the molten steel in the tundish is controlled to be 15 to 40°C.
[0025] Preferably, in step S2, during the heating and rolling process, the heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3 to 6 hours, the final rolling temperature is ≥850°C, and air cooling or slow cooling is adopted after rolling.
[0026] Preferably, in step S6, the preheating temperature is 400-550°C, and the preheating time is ≥0.5h; and the temperature of the galvanizing solution used in the hot-dip galvanizing is 400-530°C.
[0027] Preferably, the thickness of the zinc layer on the surface of the high-strength seawater corrosion-resistant chain is 10 to 150 μm.
[0028] Preferably, the microstructure of the high-strength seawater corrosion-resistant chain is needle-shaped tempered martensite and dispersed carbides; the size of the carbides is less than 300 nm.
[0029] Preferably, the performance of the high-strength seawater corrosion-resistant chain meets the following requirements: yield strength Rp 0.2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is less than 0.2g / m 2 .h.
[0030] In the high-strength seawater corrosion-resistant chain steel of the present invention, the design principles of each chemical element are as follows:
[0031] C: In the high-strength seawater corrosion-resistant chain steel of the present invention, C is an element necessary to ensure the strength of the steel. Increasing the C content in the steel will increase the non-equilibrium structural transformation ability of the steel, thereby significantly improving the strength of the steel; in the present invention, the diffusion of the C element in the steel can be suppressed by the quenching and tempering heat treatment process to form a shear-type martensitic phase transformation, thereby significantly improving the strength of the steel. However, for the present invention, the C content in the steel should not be too high. Too high a C content will have an adverse effect on the plasticity and toughness of the steel, and will significantly increase the carbon equivalent of the material and deteriorate the welding performance of the steel. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of the C element is controlled to be between 0.25 and 0.35%.
[0032] Si: In the high-strength seawater corrosion-resistant chain steel of the present invention, Si element can be dissolved in the steel and play a role of solid solution strengthening, which can significantly improve the yield strength, fatigue strength and hardness of the steel. During the corrosion process, Si mainly exists in the spinel oxide as a divalent oxide, making the inner rust layer dense and hindering Cl - Infiltration improves the marine corrosion resistance of steel. The solubility of Si in cementite is very low, and the Si content in steel should not be too high. When the Si content in steel is too high, not only will a carbide-free bainite structure be formed, but the brittleness of the steel will also be increased. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of Si element is controlled between 0.1 and 0.6%.
[0033] Mn: In the high-strength seawater corrosion-resistant chain steel of the present invention, the Mn element can improve the stability of austenite in the steel, and at the same time improve the hardenability of the steel. In addition, Mn can also improve the strength of martensite in the steel through solid solution strengthening, thereby improving the strength of the steel. However, it should be noted that the Mn content in the steel should not be too high. When the Mn content in the steel is too high, the austenite grains will grow easily during quenching heating, and promote the segregation of harmful elements at the grain boundaries. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of the Mn element is controlled between 0.3 and 0.9%.
[0034] Cr: In the high-strength seawater corrosion-resistant chain steel of the present invention, adding an appropriate amount of Cr element can improve the hardenability of the steel and has a secondary hardening effect. It can form a hardened martensitic structure, which is beneficial to improving the strength of the steel. In addition, Cr carbides can slow down the grain growth of the heat-affected zone at the welded joint, which is very beneficial to the welding of steel; adding an appropriate amount of Cr and Ni elements to the steel is beneficial to improving the corrosion resistance of the steel and promoting the formation of a passivation film on the surface of the steel. When there is a certain content of Cr, the corrosion resistance of the steel is significantly improved. However, the Cr content in the steel should not be too high. When the Cr content in the steel is too high, a large amount of carbides will be generated and aggregated at the grain boundaries, reducing the toughness of the material and significantly increasing the carbon equivalent, deteriorating the welding performance of the high-strength seawater corrosion-resistant chain steel. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of the Cr element is controlled between 0.3 and 1.2%.
[0035] Ni: In the high-strength seawater corrosion-resistant chain steel of the present invention, Ni is an austenite-forming element. As one of the main strengthening elements, it can exist in the steel in the form of solid solution and can be infinitely solid-solved with iron. It is not only acid-resistant, but also alkali-resistant, and has corrosion resistance to the atmosphere and salt. During the corrosion process, Ni replaces Fe ions in the form of divalent ions to form a relatively stable spinel NiFe2O4 compound. When the Ni element is used in combination with the Cr element, the hardenability of the steel can be significantly improved. In addition, adding an appropriate amount of Ni element to the steel can also reduce the C content of the eutectoid point, strengthen ferrite, refine and increase pearlite, and improve the strength of the steel without significantly affecting the plasticity of the steel. The Ni element can improve the fatigue resistance of the steel, reduce the sensitivity of the steel to notches, reduce the low-temperature brittle transition temperature of the steel, and improve the impact toughness of the steel. In addition, while improving the strength of the steel, the Ni element has less damage to the toughness, plasticity and other process properties of the steel than other alloying elements. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of the Ni element is controlled between 1.8 and 3.2%.
[0036] Mo: In the high-strength seawater corrosion-resistant chain steel of the present invention, the Mo element mainly exists in the steel in the form of solid solution, which can play a solid solution strengthening effect, is beneficial to improve the hardenability of the steel, and allows the steel to form martensite during the quenching process. At the same time, the Mo element can also improve the corrosion resistance to organic acids, sulfuric acid and sulfates, etc., and can passivate the steel surface in reducing acids and strong oxidizing salt solutions to prevent pitting of the steel in chloride solutions. However, the Mo element content in the steel should not be too high. When the Mo element in the steel is too high, the carbon equivalent of the material will be significantly increased, which is not conducive to the welding performance of the steel; in addition, Mo is also a precious alloy element, and adding excessive Mo will also lead to an increase in the alloy cost. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of the Mo element is controlled between 0.4 and 1.0%.
[0037] Al: In the high-strength seawater corrosion-resistant chain steel of the present invention, the main function of Al is deoxidation and nitrogen fixation. AlN formed by the combination of Al and N can effectively refine the grains. However, it should be noted that the Al content in the steel should not be too high. When the Al content in the steel is too high, it will affect the casting performance of the steel and damage the toughness of the steel. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of the Al element is controlled between 0.02 and 0.05%.
[0038] V: In the high-strength seawater corrosion-resistant chain steel of the present invention, V, as a strong carbide-forming element, can significantly improve the strength of the steel in the form of dispersed precipitation, and vanadium can also improve the steel's resistance to pitting corrosion. However, it should be noted that when the amount of V added to the steel is too high, the toughness and welding performance of the steel will be reduced. Based on this, in the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of V is controlled between 0.08 and 0.30%.
[0039] N: In the high-strength seawater corrosion-resistant chain steel of the present invention, N is an austenite-forming element and also an MX-type precipitate-forming element; in order to avoid the enrichment of N in the steel, it is not advisable to add too much N in the steel. Therefore, the content of N must be strictly controlled. In the high-strength seawater corrosion-resistant chain steel of the present invention, the mass percentage of N is controlled to be between 0.009 and 0.02%.
[0040] For the present invention, through the reasonable design of the main alloying elements, the influence of various alloying elements and their interactions on the microstructure, mechanical properties and corrosion resistance is fully utilized, and the microstructure of the steel of the present invention is accurately controlled to ensure that the high-strength seawater corrosion-resistant chain steel of the present invention forms a mixed structure of needle-shaped tempered martensite + diffusely distributed carbides, improve the chain steel's resistance to local seawater corrosion, and make the high-strength seawater corrosion-resistant chain steel of the present invention have both high strength and toughness-plasticity matching, and have good seawater corrosion resistance.
[0041] In a preferred embodiment, in the high-strength seawater corrosion-resistant chain steel of the present invention, among the inevitable impurities, P≤0.015%, S≤0.01%, and O≤0.002%.
[0042] In the above technical solution, the P element, the S element and the O element are all impurity elements in the steel. If technical conditions permit, in order to obtain high-strength seawater corrosion-resistant chain steel with better performance and higher quality, the content of impurity elements in the material should be reduced as much as possible.
[0043] In the high-strength seawater corrosion-resistant chain steel of the present invention, both P and S elements are unavoidable harmful impurity elements in the steel and both deteriorate the performance of the steel. Although the P element can improve the weather resistance of the steel, generally speaking, its side effects are greater. Therefore, in the present invention, the P element is controlled to satisfy: P≤0.015%, and the S element is controlled to satisfy: S≤0.01%.
[0044] Accordingly, in the present invention, the impurity element O can form oxides and composite inclusions with deoxidizing elements such as Al in the steel, which is not conducive to the performance of the steel. Therefore, in the present invention, the O element is controlled to satisfy: O≤0.002%.
[0045] Of course, in some other implementations, other harmful elements may exist in the steel, such as As, Pb, Sn, Sb, Bi and other elements. Under the requirements of national laws, regulations and standards, the content of these harmful elements should be reduced as much as possible.
[0046] During the use of the chain, the coating will wear off, causing the steel substrate to be partially exposed to the seawater environment and cause local corrosion, affecting the safe use of the chain. In order to improve the steel substrate's resistance to local seawater corrosion, the content of the main alloying elements Ni, Cr, Mo, Si and V in the steel that improve the resistance to local seawater corrosion must also meet the following requirements:
[0047] 1.3*Ni+2*Cr+7*Mo+0.5*Si+V≥8
[0048] The study found that when the content of Ni, Cr, Mo, Si and V alloying elements resistant to seawater local corrosion in steel meets 1.3*Ni+2*Cr+7*Mo+0.5*Si+V≥8, the steel matrix has excellent resistance to seawater local corrosion. Combined with the steel surface coating, it can greatly reduce the corrosion rate of steel in seawater environment; when the content of Ni, Cr, Mo, Si and V in steel 1.3*Ni+2*Cr+7*Mo+0.5*Si+V is lower than 8, the local corrosion resistance of steel is greatly reduced. When the chain coating fails due to local wear, obvious local corrosion defects will appear in the exposed steel matrix, causing local stress concentration in the chain, which directly affects the service life of the chain.
[0049] Compared with the existing production technology, the present invention has the following beneficial effects:
[0050] 1. The present invention adopts a reasonable chemical composition design, fully considers the interaction between the content of each alloy element and the local corrosion resistance of the chain steel in seawater, and improves the local corrosion resistance of the chain steel in seawater; cooperates with the optimized manufacturing process, fully utilizes the influence of various alloy elements and the processing process of the chain on the microstructure, and accurately controls the microstructure of the high-strength seawater corrosion-resistant chain steel of the present invention; after quenching heat treatment, the high-strength seawater corrosion-resistant chain steel forms a needle-shaped martensite structure. Through preheating and hot-dip galvanizing of the chain, on the one hand, fine carbides can be dispersed and precipitated in the supersaturated solid solution formed by quenching the chain steel, thereby improving the performance of the chain; at the same time, a zinc layer of a certain thickness can be formed on the surface of the chain, and the seawater corrosion resistance of the chain can be improved by the chain coating. When the chain coating fails due to wear, the anti-local corrosion design of the chain steel matrix can reduce local pitting of the steel, thereby improving the seawater corrosion resistance of the chain steel;
[0051] 2. After the zinc-plated layer is applied on the surface of the chain, the present invention can isolate the seawater corrosive medium from contacting the chain substrate, thereby improving the corrosion resistance of the chain; when the coating in some areas of the chain is worn, the anti-local corrosion design of the steel substrate can prevent local excessive corrosion during the use of the chain, thereby increasing the service life of the chain.
[0052] 3. The chemical composition and process design of the high-strength seawater corrosion-resistant chain steel of the present invention are reasonable, and the process window is wide, so that batch commercial production can be realized;
[0053] 4. The high-strength seawater corrosion-resistant chain steel of the present invention has excellent high strength and toughness and good resistance to local seawater corrosion. It can be made into high-strength corrosion-resistant structural parts and various high-performance industrial chains such as mining and mooring. It is widely used in construction machinery, mining and marine engineering and other occasions that require high-strength, toughness and corrosion-resistant steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0055] Figure 1 This is an electron microscope scanning image of the high-strength and high-seawater corrosion-resistant chain steel manufactured in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0057] The present invention provides a high-strength and high-seawater corrosion-resistant chain steel, which contains Fe and inevitable impurities, and also includes the following chemical components by mass percentage: C: 0.25-0.35%, Si: 0.1-0.6%, Mn: 0.3-0.9%, Cr: 0.3-1.2%, Ni: 1.8-3.2%, Mo: 0.4-1.0%, Al: 0.02-0.05%, V: 0.08-0.30%, and N: 0.009-0.02%.
[0058] The present invention improves the local corrosion resistance of chain steel in seawater by making full use of the influence of various alloy elements and their interactions on microstructure, mechanical properties and corrosion resistance through reasonable design of main alloy elements, and adopts optimized quenching and coating process to accurately control the microstructure of the steel of the present invention, so as to ensure that the high-strength seawater corrosion-resistant chain steel forms a mixed structure of needle-shaped tempered martensite + dispersed carbides, and the manufactured high-strength chain has both high strength and toughness-plasticity matching, and has good seawater corrosion resistance.
[0059] In a specific embodiment, the composition of the high-strength seawater corrosion-resistant chain steel meets the following requirements: 1.3*Ni+2*Cr+7*Mo+0.5*Si+V≥8, where Ni, Cr, Mo, Si, and V are the values before the percentage sign of the mass percentage content of the corresponding elements.
[0060] In the high-strength seawater corrosion-resistant chain steel, when the content of pitting-resistant alloy elements Ni, Cr, Mo, Si and V in the steel meets 1.3*Ni+2*Cr+7*Mo+0.5*Si+V≥8, the steel has excellent resistance to local seawater corrosion, and combined with its surface coating, it can greatly reduce its corrosion rate in seawater environment; when the content of Ni, Cr, Mo, Si and V in the steel 1.3*Ni+2*Cr+7*Mo+0.5*Si+V is lower than 8, the steel's resistance to local seawater corrosion is greatly reduced. When the chain coating fails due to local wear, obvious local corrosion defects will appear on the exposed steel substrate after contacting seawater, causing local stress concentration in the chain, which directly affects the service life of the chain.
[0061] In the present invention, P, S and O are all impurity elements in steel. Under the condition that technical conditions permit, in order to obtain high-strength steel with better performance and better quality, the content of impurity elements in the material should be reduced as much as possible. Among them, P and S are both unavoidable harmful impurity elements in steel, and both will deteriorate the performance of steel. Although P can improve the weather resistance of steel, its side effects are generally greater; O can form oxides and complex inclusions with deoxidizing elements such as Al in steel, which is not conducive to the performance of steel; therefore, among the unavoidable impurities, P≤0.015%, S≤0.01%, and O≤0.002%.
[0062] In a specific embodiment, the austenite grain size of the high-strength seawater corrosion-resistant chain steel is ≥ grade 7, and after quenching heat treatment and hot-dip coating treatment, the microstructure of the high-strength seawater corrosion-resistant chain steel is needle-shaped tempered martensite and dispersed carbides.
[0063] After heat treatment, the high-strength seawater corrosion-resistant chain steel has the following properties: yield strength Rp 0.2 ≥1000MPa, tensile strength R m ≥1100MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J.
[0064] After the hot-dip coating treatment, the corrosion rate of the high-strength seawater corrosion-resistant chain steel is less than 0.2g / m after 120h of 5% NaCl neutral salt spray corrosion test. 2 .h.
[0065] The present invention provides a high-strength seawater corrosion-resistant chain made of the above-mentioned high-strength seawater corrosion-resistant chain steel, and its performance meets the following requirements: Rp 0.2 ≥1000MPa, tensile strength R m ≥1100MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is ≤0.2g / m 2 .h.
[0066] The manufacturing method of the high-strength seawater corrosion-resistant chain of the present invention is simple to produce, and the obtained high-strength seawater corrosion-resistant chain has excellent high strength and toughness and good seawater corrosion resistance. The manufacturing method specifically comprises the following steps:
[0067] S1, smelting and casting;
[0068] Specifically, the smelting operation includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment; that is, smelting is carried out in an electric furnace or converter, and LF refining, VD or RH vacuum treatment is performed, wherein the vacuum treatment time is 10 to 20 minutes, and the steel is tapped for casting after the chemical composition meets the requirements of the high-strength seawater corrosion-resistant chain steel designed by the present invention; accordingly, in the casting process, a continuous casting process is adopted to cast the ingot, and the superheat of the molten steel in the tundish is controlled at 15 to 40°C, so as to finally obtain the ingot whose chemical composition meets the requirements of the high-strength seawater corrosion-resistant chain steel.
[0069] S2, hot rolling, control the compression ratio of the material ≥10;
[0070] Specifically, the ingot is heated in a heating furnace, and then taken out of the furnace and dephosphorized by high-pressure water before rolling, and the ingot is rolled into round steel of finished size, i.e., high-strength seawater corrosion-resistant chain steel; the heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3 to 6 hours, and the final rolling temperature is ≥850°C; after rolling, the ingot is air-cooled or slowly cooled to room temperature; the material compression ratio is controlled to be ≥10; the finished product size specification of the high-strength seawater corrosion-resistant chain steel is Φ30 to 150mm.
[0071] S3, ring welding: the rolled high-strength seawater corrosion-resistant chain steel is cut into round steel of fixed length, braided into single rings on the braiding machine, and then flash welded into a complete ring chain.
[0072] S4, quenching heat treatment, the heating temperature of quenching heat treatment is 850-950℃, the holding time is 1-3h, and water cooling quenching is adopted;
[0073] Specifically, the ring-welded chain is subjected to quenching heat treatment, the heating temperature of the quenching heat treatment is 850-950°C, the holding time is 1-3h, and then water-cooling quenching is performed; when the ring-welded chain is heated at high temperature, fine austenite grains are formed in the steel, and the austenite grain size is ≥7 levels; after quenching, the chain structure is transformed from the austenite structure at high temperature to a fine needle-shaped martensite structure.
[0074] S5, pickling pretreatment: The chain after quenching heat treatment is pickled for pretreatment to remove the oxide scale on the surface of the chain after quenching, and a layer of plating solution is applied on the surface of the chain to keep the surface of the chain after pickling to a certain activity, avoid oxidation of the chain during the subsequent preheating treatment, and enhance the bonding strength between the galvanized layer and the substrate.
[0075] S6, hot dip galvanizing, the chain after pickling pretreatment is preheated and then hot dip galvanized to obtain a high strength seawater corrosion resistant chain, and the temperature difference between the preheating temperature and the galvanizing solution used for hot dip galvanizing is controlled to be -30 to 30°C.
[0076] Specifically, the chain after pickling pretreatment is hot-dip galvanized. In order to prevent problems such as zinc explosion in the subsequent hot-dip galvanizing process, the chain is preheated and then hot-dip galvanized to obtain a high-strength seawater corrosion-resistant chain; the difference between the preheating temperature and the temperature of the galvanizing solution used in the hot-dip galvanizing is controlled to be -30 to 30°C, wherein the preheating temperature is 400 to 550°C, and the preheating time is ≥0.5h; the temperature of the galvanizing solution used in the hot-dip galvanizing is 400 to 530°C, and the thickness of the zinc layer on the surface of the high-strength seawater corrosion-resistant chain is 10 to 150 μm.
[0077] During the hot-dip galvanizing process, the supersaturated martensite structure formed after quenching of the chain begins to precipitate fine carbides, the strength of the chain decreases, but the elongation and impact toughness begin to increase. The fine needle-shaped martensite is conducive to the precipitation of fine dispersed carbides from the steel during hot-dip galvanizing, and the carbide size is less than 300nm, so as to obtain a high-strength seawater corrosion-resistant chain with excellent strength and toughness.
[0078] The microstructure of the high-strength seawater corrosion-resistant chain manufactured above is needle-shaped tempered martensite and dispersed carbides; the size of the carbides is less than 300nm.
[0079] The performance of the above high strength seawater corrosion resistant chain meets the following requirements: yield strength Rp0 .2 ≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is less than 0.2g / m 2 .h.
[0080] The present invention makes full use of the influence of various alloy elements and manufacturing processes on microstructure and corrosion resistance through reasonable design of alloy elements and optimized manufacturing process, accurately controls the microstructure of high-strength seawater corrosion-resistant chain steel, and improves the seawater local corrosion resistance of the chain steel matrix. After quenching heat treatment, the high-strength seawater corrosion-resistant chain steel forms a needle-shaped martensite structure. Through hot-dip galvanizing of the quenched chain, on the one hand, fine and dispersed carbides can be precipitated during hot-dip galvanizing of the chain steel, thereby improving the toughness of the chain; a zinc coating of a certain thickness is formed on the surface of the chain in combination with the anti-pitting component design of the steel matrix, and the seawater corrosion resistance of the chain is improved through the chain coating. When the chain coating fails due to wear, the seawater local corrosion resistance design of the chain steel matrix can reduce the local corrosion of the steel, thereby improving the seawater corrosion resistance of the chain steel.
[0081] In the manufacturing method of the high-strength seawater corrosion-resistant chain of the present invention, the quenching and tempering process of the traditional chain is combined with the hot-dip galvanizing process, the tempering process of the chain is omitted, and the chain is fully utilized during the hot-dip galvanizing process to realize the precipitation of carbides in the steel, thereby realizing the efficient production of the high-strength seawater corrosion-resistant chain, so that the high-strength seawater corrosion-resistant chain steel and the chain of the present invention have higher strength and toughness-plasticity matching, and have good corrosion resistance.
[0082] The high-strength seawater corrosion-resistant chain steel and chain and the manufacturing method thereof of the present invention are further introduced below with reference to specific examples.
[0083] Example
[0084] Combined with Table 1, Table 2-1 and Table 2-2, the high-strength seawater corrosion-resistant chain steel and chain of Example 1-6 adopt the following steps:
[0085] (1) Smelting and continuous casting are performed according to the chemical composition shown in Table 1 below to obtain ingots. The smelting can be performed by electric furnace or converter smelting, and then LF refining and VD or RH vacuum treatment are performed. The vacuum treatment time is 10 to 20 minutes. After the composition meets the requirements, the steel is tapped and then continuously cast into ingots. During the continuous casting process, the superheat of the molten steel in the tundish is controlled to be 15 to 40°C.
[0086] (2) Heating rolling: The ingot is heated in a heating furnace and then dephosphorized by high-pressure water before being processed into round steel of finished product size, i.e. high-strength seawater corrosion-resistant chain steel. The size specification range of the rolled product is Φ30-150mm, and the material compression ratio is controlled to be ≥10. During the rolling process, the heating temperature of the ingot is controlled to be ≥1150℃, the heating time is 3-6h, and the final rolling temperature is ≥850℃; after rolling, it is air-cooled or slowly cooled to room temperature.
[0087] (3) Ring welding: The high-strength seawater corrosion-resistant chain steel is cut into round steel of fixed length and braided into a single ring on a braiding machine, and then flash welded into a complete ring chain.
[0088] (4) Quenching heat treatment: The chain after ring welding is quenched and heat treated, the heating temperature of the quenching heat treatment is controlled to be 850-950°C, the holding time is 1-3h, and then water-cooled quenching is performed.
[0089] (5) Pickling pretreatment: Pickle the chain after quenching to remove the oxide scale on the chain surface. Then preheat the chain to prevent zinc explosion and other problems during the subsequent hot-dip galvanizing process. The chain preheating temperature is 400-550℃, the preheating time is ≥0.5h, and the preheating temperature of the preheating treatment and the temperature difference of the galvanizing solution used for subsequent hot-dip galvanizing are -30℃ to 30℃.
[0090] (6) Hot-dip galvanizing: The preheated chain is hot-dip galvanized at a temperature of 400 to 530°C, and the thickness of the zinc layer on the chain surface is controlled to be 10 to 150 μm.
[0091] Combined with Table 1, Table 2-1, and Table 2-2, the chemical composition design and related process parameters of the high-strength seawater corrosion-resistant chain steel prepared in Example 1-6 meet the design specification requirements of the present invention. The comparative steel of Comparative Example 1-2 is a finished steel from different manufacturers, and its chemical composition design can be seen in Table 1. Its manufacturing process is different from that of Example 1-6. The parameters of the heat treatment process used in Comparative Example 1-2 are shown in Table 2-1 and Table 2-2.
[0092] Table 1 Chemical composition of chain steel (wt.%, the balance is Fe and other impurities except P and S)
[0093]
[0094] Table 2-1 Process parameters of the examples and comparative examples during the preparation process
[0095]
[0096] Table 2-2 Process parameters of the embodiments and comparative examples during the preparation process
[0097]
[0098] The finished chains of Examples 1-6 and the comparative chains of Comparative Examples 1-2 were collected and their performances were tested respectively to obtain the performances of the finished steels of the Examples and Comparative Examples;
[0099] The finished chains obtained in the above-mentioned Examples 1-6 and the comparative chains in Comparative Examples 1-2 were subjected to neutral salt spray corrosion test, tensile test and impact performance test, respectively, and the test results are listed in Table 3.
[0100] The specific detection methods for relevant neutral salt spray corrosion test, tensile test and impact test are as follows:
[0101] (1) The neutral salt spray corrosion test is carried out by the following steps: 100 mm long round steel is taken from the finished chain of Examples 1-6 and the chain of Comparative Examples 1-2 after being treated with coating as a salt spray corrosion specimen, and both end faces are sealed with silicone rubber. A 5wt% NaCl salt spray corrosion test is carried out according to GB / T 10125 standard (laboratory temperature 35°C, saturated barrel temperature 47°C, corrosive medium is 5wt.% NaCl aqueous solution, pH=6.5, the test sample is at a 20° angle in the longitudinal direction, the test time is 120h, continuous spraying is adopted, and the salt spray deposition amount is 1.5mL / (h·80cm2)). After the 120h neutral salt spray test, the test sample is taken out, the silicone rubber at both ends is peeled off, the surface corrosion products are removed, the sample is blown dry and the mass is weighed and recorded as M', and then the salt spray corrosion rate R of each embodiment and comparative example sample is calculated:
[0102] R=(M-M') / (S·T)
[0103] Where M is the initial mass of the sample, with the dimension of g; M' is the mass of the sample after the corrosion products are removed and blown dry, with the dimension of g; S is the corrosion test area of the sample, with the dimension of m 2 ; T is the corrosion time, the dimension is h; the salt spray corrosion rate R is g / m 2 .h.
[0104] Tensile test: The finished chains of Examples 1-6 after coating and the comparative chains of Comparative Examples 1-2 were sampled according to the national standard GB / T 2975 and made into tensile specimens. The tensile performance test was carried out according to the national standard GB / T 228.1 to measure the yield strength Rp of the high-strength seawater corrosion-resistant chains of Examples 1-6 and the comparative chains of Comparative Examples 1-2. 0.2 , tensile strength R m , elongation A and section shrinkage Z.
[0105] Impact test: The finished chains of Examples 1-6 and the comparative chains of Examples 1-2 were sampled according to the national standard GB / T 2975 and made into impact specimens. The impact performance test was carried out according to the national standard GB / T 229 to measure the Charpy impact energy A of the high-strength chains of Examples 1-6 and the comparative chains of Comparative Examples 1-2 at -20°C. kv .
[0106] Table 3 Performance of the chains of the embodiments and comparative examples
[0107]
[0108] As shown in Table 3, the high-strength seawater corrosion-resistant chain in the embodiment of the present invention has excellent comprehensive performance, and its yield strength Rp 0.2 Between 1066 and 1185 MPa, the tensile strength Rm Between 1183 and 1285 MPa, elongation A ≥ 14%, section shrinkage Z ≥ 50%, -20℃ Charpy impact energy A kv ≥60J.
[0109] As shown in Table 1 and Table 3, the contents of alloying elements Ni, Cr, Mo, Si, and V in the chemical composition of the steel in Comparative Example 1-2 cannot satisfy 1.3Ni+2Cr+7Mo+0.5Si+V≥8, and the seawater corrosion resistance of the present technology cannot be achieved.
[0110] As shown in Table 3, the neutral salt spray corrosion rate of the high-strength seawater corrosion-resistant chain of Examples 1-6 of the present invention is ≤0.19 g / m 2 .h, which is much lower than the neutral salt spray corrosion rate of the comparison chain in Comparative Example 1-2. It can be seen that the corrosion resistance of the high-strength seawater corrosion-resistant chain obtained by heat treatment and hot-dip galvanizing of the high-strength seawater corrosion-resistant chain steel of the present invention is significantly better than the existing comparison chain selected in Comparative Example 1-2.
[0111] Figure 1 This is a scanning electron microscope image of the microstructure of the chain steel in Example 1. Figure 1 As shown, in Example 1, the microstructure of the chain steel after quenching + coating treatment is needle-shaped tempered martensite, and fine dispersed nano-scale carbides are precipitated on the martensite matrix, and the carbide size is less than 300um. The fine nano-scale carbides can greatly improve the strength and toughness of the steel, thereby obtaining a high-strength and high-toughness chain steel with excellent performance.
[0112] In summary, the present invention improves the ability of the steel matrix to resist local seawater corrosion through a reasonable chemical composition design, and combines the chain heat treatment and the subsequent galvanizing process to form an optimized quenching hot-dip galvanizing process, so as to obtain a high-strength seawater corrosion-resistant chain with excellent performance. The high-strength seawater corrosion-resistant chain of the present invention has excellent comprehensive performance. It not only has high strength, but also has excellent toughness and plasticity matching. It is made into a high-strength seawater corrosion-resistant chain with excellent corrosion resistance, which can well solve the problem of the existing chain that the service life is affected by the mismatch of strength, toughness, plasticity and corrosion resistance. The high-strength seawater corrosion-resistant chain steel of the present invention can be made into various high-performance industrial chains such as mooring and mining, and is widely used in marine engineering, engineering machinery, mines and other occasions that require high-strength, toughness and high-corrosion-resistant chains.
[0113] It should be noted that those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A high-strength seawater corrosion-resistant chain steel, characterized in that: It includes the following chemical components in mass percentage: C: 0.25-0.35%, Si: 0.1-0.6%, Mn: 0.3-0.9%, Cr: 0.3-1.2%, Ni: 1.8-3.2%, Mo: 0.4-1.0%, Al: 0.02-0.05%, V: 0.08-0.30%, N: 0.009-0.02%, and the balance is iron and unavoidable impurities.
2. The high-strength seawater corrosion-resistant chain steel according to claim 1, characterized in that: Its composition meets the following requirements: 1.3*Ni+2*Cr+7*Mo+0.5*Si+V≥8, wherein Ni, Cr, Mo, Si, and V are the values before the percentage sign of the mass percentage content of the corresponding elements.
3. The high-strength seawater corrosion-resistant chain steel according to claim 1, characterized in that: Among the unavoidable impurities, P≤0.015%, S≤0.01%, and O≤0.002%.
4. The high-strength seawater corrosion-resistant chain steel according to claim 1, characterized in that: The austenite grain size of the high-strength seawater corrosion-resistant chain steel is ≥ grade 7; after quenching heat treatment and hot-dip plating treatment, the microstructure of the high-strength seawater corrosion-resistant chain steel is needle-shaped tempered martensite and dispersed carbides.
5. The high-strength seawater corrosion-resistant chain steel according to claim 1, characterized in that: After quenching heat treatment, its performance meets the following requirements: yield strength Rp 0.2 ≥1000MPa, tensile strength R m ≥1100MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J.
6. The high-strength seawater corrosion-resistant chain steel according to claim 1, characterized in that: After the surface of the high-strength seawater corrosion-resistant chain steel is treated by hot-dip plating, the corrosion rate is ≤0.2g / m after a 5% NaCl neutral salt spray corrosion test for 120 hours. 2 .h.
7. A high-strength seawater corrosion-resistant chain manufactured using the high-strength seawater corrosion-resistant chain steel according to any one of claims 1 to 6, characterized in that: Its performance meets: Rp 0.2 ≥1000MPa, tensile strength R m ≥1100MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is ≤0.2g / m 2 .h.
8. A method for manufacturing a high-strength seawater corrosion-resistant chain as claimed in claim 7, characterized in that: The following steps are involved: S1, smelting and casting; S2, hot rolling, control the compression ratio of the material ≥10; S3, ring welding; S4, quenching heat treatment, the heating temperature of quenching heat treatment is 850-950℃, the holding time is 1-3h, and water cooling quenching is adopted; S5, pickling pretreatment; S6, hot dip galvanizing, the chain after pickling pretreatment is preheated and then hot dip galvanized to obtain a high strength seawater corrosion resistant chain, and the temperature difference between the preheating temperature of the preheating treatment and the galvanizing solution used for the hot dip galvanizing is controlled to be -30 to 30°C.
9. The method for manufacturing a high-strength seawater corrosion-resistant chain according to claim 8, characterized in that: In the step S1, the smelting includes electric furnace or converter smelting, LF refining, VD or RH vacuum treatment; the casting adopts a continuous casting process, wherein the vacuum treatment time of the VD or RH vacuum treatment is 10 to 20 minutes; during the casting process, the superheat of the molten steel in the tundish is controlled to be 15 to 40°C; In the step S2, during the heating and rolling process, the heating temperature of the ingot is controlled to be ≥1150°C, the heating time is 3 to 6 hours, the final rolling temperature is ≥850°C, and air cooling or slow cooling is adopted after rolling; In the step S6, the preheating temperature is 400-550°C, and the preheating time is ≥0.5h; the temperature of the galvanizing solution used in the hot-dip galvanizing is 400-530°C.
10. The method for manufacturing a high-strength seawater corrosion-resistant chain according to claim 8, characterized in that: The thickness of the zinc layer on the surface of the high-strength seawater corrosion-resistant chain is 10 to 150 μm.
11. The method for manufacturing a high-strength seawater corrosion-resistant chain according to claim 8, characterized in that: The microstructure of the high-strength seawater corrosion-resistant chain is needle-shaped tempered martensite and dispersed carbides; the size of the carbides is less than 300nm.
12. The method for manufacturing a high-strength seawater corrosion-resistant chain according to claim 8, characterized in that: The performance of the high-strength seawater corrosion-resistant chain meets the following requirements: yield strength Rp0.2≥1050MPa, tensile strength R m ≥1200MPa, elongation A≥14%, section shrinkage Z≥50%, -20℃ Charpy impact energy A kv ≥60J; After 120h of 5% NaCl neutral salt spray corrosion test, the corrosion rate is less than 0.2g / m 2 .h.
Citation Information
Patent Citations
Ultra high strength ship plate steel and production method thereof
CN101906591B
Ultra high-strength structural steel and method for producing ultra high-strength structural steel
CN103348020A
Steel for high-strength, high-toughness, corrosion-resistant chains and heat treatment method thereof
CN106521356B
High-strength high dampness and heat sea atmospheric environment resistant weathering resistant steel and preparing method
CN106756476A
High-intensity and corrosion-resistant Pb-Sn composite coating binding band and production method thereof
CN104097848A
Cited By
Corrosion-resistant chain plate steel as well as preparation method and application thereof
CN120796850A